Current topics in developmental biology. - Ordahl, Charles P. (Current topics in developmental biology, 2000)
The chapters contained in this two-volume set provide a broad perspective on the novel strategies and conceptual paradigms that drive the current resurgence of interest in somitogenesis - the process by which somites form and elaborate differentiated tissues and structures. Because somites are a ubiquitous feature of vertebrate embryos, they can be studied in a variety of experimental animal models including those amenable to genetic (zebrafish, mammalian), molecular/genetic (mammalian, avian) as well as those already well established for classical experimental embryological and cell biological studies (amphibians, avian). The wide variety of experimental approaches to somitogenesis that are presented in these volumes will leave the reader with a broad perspective on how current research in somitogenesis is helping to solve fundamental questions in vertebrate development and morphogenesis.